Patient-reported Outcome Measures and Decision Regret After Prostate-specific Membrane Antigen–targeted Radioguided Surgery for Oligorecurrent Prostate Cancer - Fabian Falkenbach; Giovanni Mazzucato; Zhe Tian; Pierre I. Karakiewicz; Markus Graefen; Thomas Steuber; Derya Tilki; Daniel Koehler; Burkhard Beyer; Pierre Tennstedt; Sophie Knipper; Lars Budäus; et al. (European Urology Open Science)
Background and objective: In patients with oligorecurrent prostate cancer (PCa), prostate-specific membrane antigen–targeted radioguided surgery (PSMA-RGS) prolongs treatment-free survival. Data on patient-reported outcome measures (PROMs) are lacking. Methods: A retrospective assessment of validated PROMs (12-item Short Form Health Survey [SF-12], 26-item Expanded Prostate Index Composite, and Decision Regret Scale [DRS]) was performed before and after PSMA-RGS for oligorecurrent PCa. Mixed models were used. Key findings and limitations: A total of 373 patients were analyzed at a median (interquartile range [IQR]) age of 66 (61, 70) yr and prostate-specific antigen of 0.8 (0.4, 1.5) ng/ml. Six months after PSMA-RGS, the median (IQR) scores for the PROMs were as follows: SF-12 physical 54 (49, 56), SF-12 mental 53 (43, 56), urinary incontinence 86 (52, 100), urinary irritation 94 (88, 100), sexual 27 (9, 57), hormonal 90 (79, 100), and bowel 96 (83, 100). Only the sexual score decreased in a significant fashion from baseline over time (median [IQR], 17 [8,38]) after 3 yr vs 37 [13, 63] at baseline, p = 0.01). The decision regret remained low (median [IQR] DRS at 1 yr: 5 [0, 20]). More than 90% of the patients reported that PSMA-RGS was the correct decision after 1 yr. Conclusions and clinical Implications: We recorded no significant decrease in quality of life or any functional status domain, except sexual. While decision regret was low, sexual functioning might deteriorate further. Patient summary: No significant deterioration in health-related quality of life was reported after removing early prostate cancer metastases. Very few patients expressed remorse about their decision for salvage surgery.